(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2018)
The process of environmental and economic evaluation is one of the most important means which is available to compare the substitutes at the localizing of projects, and thus changing these projects into more benefit projects , as regards to economy. The environmental process is an important means to the integrate of external cost in the standards of economic benefit , and to give the project the right of a defined pollution inters in the framework of local and investment map be a basic for environmental policy which has the ability to ensure a complete environmental sanitation reaching to the application of the polluter –pays principle. The research discusses many points : The concept of environmental pollution in economy and its external effects ( as an external ) and The importance of the environmental evaluation also The effect of projects on the environment and economic income of environmental evaluation .and The role of environmental and economic evaluation in localizing of industrial projects in Syria . أهمية التقييم الاقتصادي – البيئي في تمركز المشروعات الصناعية في سورية تعد عملية التقييم الاقتصادي-البيئي من أهم الوسائل المتاحة لمقارنة البدائل عند تمركز المشروعات ، وبالتالي تحويلها إلى مشاريع أكثر جدوى من الناحية الاقتصادية. ويعد التقييم البيئي أداة ضرورية لإدماج التكلفة الخارجية في معايير الجدوى الاقتصادية ، وتمليك المشروع حق تلويث محدد يدخل في إطار خارطة استثمارية محلية تكون أساساً لسياسة بيئية قادرة على أن تضمن إصحاح بيئي متكامل وصولاً إلى تطبيق مبدأ الملوث يدفع. بناءً على ما تقدم جاء هذا البحث ليسلط الضوء على دور التقييم الاقتصادي-البيئي في تمركز المشروعات الصناعية في سورية ، متناولاً الموضوع من خلال الحديث عن الآثار الخارجية ومفهوم التلوث البيئي في الاقتصاد ( كتكلفة خارجية ) وأهمية التقييم البيئي ، وكذلك أثر المشروعات على البيئة والعائد الاقتصادي للتقييم البيئي و دور التقييم الاقتصادي – البيئي في تمركز المشروعات الصناعية في سورية .